New and rare Laboulbenialis (Ascomycetes) from the Białowieża Forest (NE Poland) - Tomasz Majewski (Acta Mycologica, 2014)
This paper presents descriptions of some interesting species of the Laboulbeniales collected by the author in the Białowieża Forest and its foreland (NE Poland) in the period 1994-1998. Among them are 18 determined species new for Poland, four new for science (Corethromyces bialowiezensis sp.n. on Tachyporus solutus, Cryptandromyces bryaxidis sp.n. on Bryaxis bulbifer, Euphoriomyces unilateralis sp.n. on Agathidium atrum, and Phaulomyces ptilii sp.n. on Ptilium affine), and two or three species new for Europe (Peyritschiella geminata Thaxter, Zodiomyces subseriatus Thaxter and perhaps Laboulbenia epithricis Thaxter). Four species are probably new for science but the collected material is too scanty to describe them. Additionally, details concerning morphology or systematic position of some species known already from Poland are supplemented. These data essentially complemented a recent description of Polish species of the group (Majewski 1994).